Embryonic proteoglycans regulate monoamines in the rat frontal cortex and hippocampus in Alzheimer's disease-like pathology. (November 2020) - Chavushyan, Vergine; Matinyan, Senik; Danielyan, Margarita; Aghajanov, Michail; Yenkoyan, Konstantin
Abstract: Using the rat Alzheimer's disease (AD)-like model we have analyzed the hippocampal short-term potentiation, levels of monoamines, and morphological changes in the hippocampal and cortical neurons after the administration of proteoglycans of embryonic origin (PEG). Results showed that the levels of monoamines and especially norepinephrine in the target AD brain structures were found elevated, except serotonin, which was unaffected in the hippocampus, but decreased in the frontal cortex. These changes were accompanied by the substantial structural damage of cortical and hippocampal neurons. PEG was able to reverse most of these changes. In addition, PEG administration had regime-dependent effects on a short-term potentiation pattern of hippocampal neurons. The elevated levels of key elements of brain monoaminergic system in the model of AD support the hypothesis of the important role of monoamines in the excessive synaptic excitation resulting in cognitive dysfunction in AD brain. The neuroprotective effect of PEG, as manifested by the recovery of the monoaminergic system, suggests this bioactive substance as a perspective therapeutic agent for the treatment of AD. Graphical abstract: Illustration of the changes at Alzheimer's disease rat model initiated by intracerebroventricular injection of amyloid beta 25–35 and modulation of these effects by proteoglycans of embryonic (PEG), underlying one of the possible neuroprotective mechanisms of PEG action. Image 1 Highlights: Administration of Aβ25–35 leads to the increased levels of monoamines in cerebral cortex and hippocampus and their damage. In line with severe damage of cortical and hippocampal neurons Aβ25–35 disturbs the short-term potentiation in hippocampus. PEG prevents the increase of monoamines in the frontal cortex and hippocampus at AD-like neurodegeneration. PEG has substantial effects on short-term potentiation changes in hippocampal neurons.